2001
DOI: 10.1097/00006454-200101000-00041
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ofloxacin and other otic preparations for acute otitis media in patients with tympanostomy tubes

Abstract: Otorrhea occurs in 21 to 50% of all children with tympanostomy tubes in the United States. More than 1 million children annually undergo tubomyringotomy, constituting placement of more than 2 million tympanostomy tubes each year. The organisms typically responsible for otorrhea are the same as those that cause otitis media in very young children, including Streptococcus pneumonia, Haemophilus influenzae and Moraxella catarrhalis. Drainage from tympanostomy tubes in older children involves organisms that coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 8 publications
0
10
0
2
Order By: Relevance
“…In fact, our study showed that a higher cure rate was registered for ofloxacin over the combination of antibiotic-steroid preparations. The estimate, however, lacks precision (95% CI = 1.52, 4.90); and in the light of other reports claiming more rapid resolution of otorrhea in CSOM patients given other ototopical antibiotic and steroid combinations [22] these data must be interpreted only as far as the available data are concerned.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In fact, our study showed that a higher cure rate was registered for ofloxacin over the combination of antibiotic-steroid preparations. The estimate, however, lacks precision (95% CI = 1.52, 4.90); and in the light of other reports claiming more rapid resolution of otorrhea in CSOM patients given other ototopical antibiotic and steroid combinations [22] these data must be interpreted only as far as the available data are concerned.…”
Section: Discussionmentioning
confidence: 69%
“…On the other hand, ofloxacin, which has good in vitro and in vivo activity against these pathogens [3], demonstrated a significantly higher cure rate for both otitis types (draining tympanostomy tube and CSOM). Furthermore, instillation of antibiotics into the middle ear has the advantage of delivering very high concentrations of the drug to the middle ear: 0.3% ofloxacin otic solution attains local concentrations of 3 mg/ml, which far exceeds the minimum inhibitory concentrations (more than 1,000-fold) in comparison with those achieved systemically [22]. The statistically favorable result obtained with 0.3% ofloxacin otic solution in terms of overall cure rate and resolution of otorrhea versus the other comparator medications (table 2) confirm the effectiveness of ototopical antibiotics for CSOM and draining tympanostomy tube.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous forms of treatments including topical preparations, systemic therapies and office-based debridement [1,4]. Though several options exist for the treatment otitis externa, the use of ototopical agents in the setting of open middle ear space created by tympanostomy tube insertion or tympanic membrane perforation continues to be debated [4][5][6][7][8][9][10][11][12]. However, the use of ototopicals in the fluoroquinolone class is now more widely accepted.…”
Section: Introductionmentioning
confidence: 99%
“…Nas crianças muito pequenas, os organismos tipicamente responsáveis pela otorréia são os mesmos da OMA, incluindo Streptococcus pneumoniae, Haemophilus influenzae e Moraxella catarrhalis. Nas crianças maiores, a otorréia costuma ser causada por organismos que colonizam a orelha externa, como Pseudomonas aeruginosa e Staphylococcus aureus 2 .…”
Section: Veja Artigo Relacionado Na Página 475unclassified